Markers of Inflammation and Monoamine Metabolism Indicate Accelerated Aging in Bipolar Disorder - van den Ameele, Seline; Fuchs, Dietmar; Coppens, Violette; de Boer, Peter; Timmers, Maarten; Sabbe, Bernard; Morrens, Manuel (Frontiers in Psychiatry, 2018)
Background: A mild pro-inflammatory status accompanies bipolar disorder (BD). Inflammation can cause a shift in monoamine metabolism, thereby activating more cytotoxic pathways. The extent to which low-grade inflammation in BD interacts with monoamine metabolism and how this accords to aging and clinical course is unknown. Objectives: We evaluated the presence of alterations in inflammation and monoamine metabolism in BD throughout different mood states and the role of aging therein. Methods: Sixty-seven patients with BD were included during an acute mood episode, either depressive (n=29), (hypo)manic (n=29) or mixed (n=9). Plasma levels of inflammatory markers (tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-y), interleukin-6 (IL-6) and C-reactive protein (CRP)) and markers of monoamine metabolism (neopterin, tryptophan, kynurenine, phenylalanine and tyrosine) were measured repeatedly during a follow-up of 8 months. Levels in patients were compared to controls (n=35) and correlated to HDRS-17 and YMRS scores. Spearman correlations and linear mixed model analysis were used for statistical analysis. Results: Forty-nine patients and 30 controls (age range: 22-62y) completed the study. No significant differences in inflammatory markers were found between patients and controls overall. Tryptophan, tyrosine and phenylalanine levels were lower in patients. In both patients and controls, markers of inflammation correlated only weakly with markers of monoamine metabolism, but correlations representative for activity of cytotoxic pathways in monoamine metabolism were more pronounced in patients. In patients, but not in controls, older age was associated with increases in inflammatory markers (IL-6, CRP, neopterin) and the kynurenine/tryptophan ratio. None of the biological markers correlated significantly with mood symptom severity. Conclusion: Our data suggest an increased susceptibility of patients with BD to develop a pro-inflammatory state and to shift monoamine metabolism towards more cytotoxic pathways. These findings are in support of the theory of neuroprogression and accelerated aging in BD. Since associations between biological markers and clinical characteristics are limited, it remains to be determined if alterations in biological markers are due to a disease effect or rather are a consequence of confounding factors.